Pengaruh Edukasi Kesehatan Terhadap Kemampuan Kognitif Orangtua Dalam Menstimulasi Tumbuh Kembang Anak Usia Prasekolah di Paud At-Taufiq Manado - Jumiati Buton; Helly katuuk; Sri Wahyuni (STIKES Columbia Asia Medan, 2023)
At pre-school age, parents generally pay significant attention to their development, especially in aspects of children's development. This happens because pre-school age is a golden age which is often called the golden age. Cognitive development cannot take place optimally without stimulus or incentives given to pre-school children. The aim of this research is to determine the effect of health education on parents' cognitive abilities in stimulating the growth and development of preschool children at Paud At-Taufiq Manado. This research method uses a design with a One Group Pre Test - Post Test Design approach. The population in the study was 32 respondents using the Total Sampling technique, the research used questionnaire sheets and Sap. The results of the research using the paired T-test obtained a P value (0.000) or < α (0.05), which means that there is an influence of health education on parents' cognitive abilities in stimulating the growth and development of preschool children at At-Taufiq Manado Paud. The conclusion in this research is that there is a cognitive influence of parents in stimulating the growth and development of pre-school children. At At-Taufik Paud Manado. It is hoped that the results of this research can provide knowledge to parents.